Efektivitas Pusat Kegiatan Belajar Masyarakat (PKBM) Permata Bunda Sebagai Lembaga Pendidikan Nonformal dalam Upaya Pengentasan Wajib Belajar Sembilan Tahun - Fismanelly Fismanelly; Herman Herman; Syahril Syahril (UIN Imam Bonjol Padang, 2022)
The aim of this research is to obtain information and to see the effectiveness of Permata Bunda PKBM as a non-formal education institution in an effort to reduce nine-year compulsory education. This research was conducted using a qualitative approach, with a case study approach. This research was conducted at the Permata Bunda Community Learning Activity Center (PKBM), which is located in Jorong Bariang Nagari, Lubuk Gadang Utara, Sangir sub-district, South Solok Regency. The results showed that PKBM Permata Bunda has been effective as a non-formal educational institution in helping people who have dropped out of school, this can be seen from the educators and education staff who are set according to qualifications, the curriculum used, the learning process that makes it easier for citizens to learn, the curriculum that used and assessment in accordance with predetermined criteria. The existing facilities and infrastructure at Permata Bunda PKBM are adequate to carry out the learning process, such as the completion of learning facilities and buildings as well as secretarial facilities.